No Surrender. No Challenge. No Protest Paradigm: A Content Analysis of the Canadian News Media Coverage of the "Yellow Vest Movement" and the "United We Roll Convoy". (5th November 2020) - De Cillia, Brooks; McCurdy, Patrick
Abstract: This study's exhaustive content analysis ( N = 538) examines how Canada's mainstream news media covered the nascent yellow vest movement from the first Canadian protests in December 2018 culminating in the February 2019 cross‐country United We Roll convoy. We demonstrate that Protest Paradigm scholarship does not offer a useful analytic for understanding the coverage of this right‐wing social movement whose tactics were banal and law abiding. Furthermore, we argue that Canadian news media coverage of the protest movement was largely uncritical and decidedly hegemonic, raising questions about normative watchdog conceptions of the news media in Canadian democracy. Résumé: Grâce` à une analyse de contenu ( N = 538), cet article examine comment les médias d'information grand public du Canada ont couvert le mouvement naissant des gilets jaunes depuis les premières manifestations canadiennes en décembre 2018 qui ont culminé avec le convoi international United We Roll de février 2019. Nous démontrons que la bourse Protest Paradigm n'offre pas une analyse utile pour comprendre la couverture de ce mouvement social de droite dont les tactiques étaient banales et respectueuses de la loi. De plus, nous soutenons que la couverture médiatique canadienne du mouvement de protestation était en grande partie non critique et résolument hégémonique, soulevant des questions sur les conceptions normatives de surveillance des médias dans la démocratie canadienne.